Legacy brominated flame retardants in human milk from the general population in Beijing, China: Biomonitoring, temporal trends from 2011 to 2018, and nursing infant's exposure assessment - Zhao, Xuezhen; Shi, Zhixiong (Chemosphere (Oxford), 2021)
Three kinds of legacy brominated flame retardants (BFRs), including eight polybrominated diphenyl ether (PBDE) congeners, tetrabromobisphenol A (TBBPA), and three hexabromocyclododecane (HBCDD) isomers, were analyzed in 105 human milk samples collected in 2018 from Beijing, China. The tested BFRs all showed high detection frequencies, and HBCDD was the most abundant BFR, with a median level of 7.64 × 103 pg/g lipid, followed by BDE-153 (389 pg/g lipid), BDE-209 (283 pg/g lipid), and TBBPA (271 pg/g lipid). By comparing the results of the present study with those of our previous Beijing human milk surveys conducted in 2014 and 2011, the contamination of TBBPA and HBCDD increased steadily from 2011 to 2018, whereas that of PBDEs decreased sharply during this period. Our results suggested that the production and consumption of BFRs in China have shifted from PBDEs to other FRs. Education level and the consumption of animal-derived foods such as eggs and meat were identified as major influencing factors for some BFRs. For nursing infants, the median levels of lower bound BFR daily intake via human milk ingestion ranged from 4.62 × 10−2 ng/kg bw/day for BDE-154 to 30.6 ng/kg bw/day for HBCDD. The daily intake of most BFRs by breastfeeding is unlikely to pose significant health risks for Beijing nursing infants. However, the minimum margin of exposure (MOE) of HBCDD was below its threshold value, which indicated that its daily intake might raise health concerns for some breastfed infants. [Display omitted] •PBDEs, TBBPA, and HBCDD were tested in a Beijing human milk survey conducted in 2018.•Levels of PBDEs gradually decreased from 2011 to 2018 due to the decline of BDE-209.•Levels of TBBPA and HBCDD in human milk rose significantly from 2011 to 2018.•Daily PBDE/TBBPA intake was unlikely to pose significant health risks for infants.•Daily HBCDD intake may cause health concerns for some breastfed infants.